#### Answer

t = $\frac{13}{3}$

#### Work Step by Step

t - 6t = -13 + t - 3t
-5t = -13 - 2t
-3t = -13
t = $\frac{13}{3}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

t = $\frac{13}{3}$

t - 6t = -13 + t - 3t
-5t = -13 - 2t
-3t = -13
t = $\frac{13}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.